The political economy of a divided Ireland - Michie, J; Sheehan, M (Oxford University Press, 1998)
For a peace process in Ireland to succeed it will require an active transition away from the underlying causes of conflict—not just the partition of the country, but the inequalities of opportunities and employment between the communities in Northern Ireland. This requires the restructuring of existing unequal arrangements. If this restructuring is not to be at the expense of the Protestant community, public intervention will be needed to ensure that opportunities for the Protestant community can be developed alongside the necessary catching-up of the previously disadvantaged community. Otherwise any type of future transition process risks grinding to a halt.